Proportionality, balancing, and rights: Robert Alexy's theory of constitutional rights - Sieckmann, Jan-Reinard (Law and philosophy library, 2021)
Constitutional Rights, Proportionality, and Argumentation -- The Role of Morality in Balancing Constitutional Rights -- Constitutional discretion and proportionality: the positivistic weight formula -- Proportionality and meta-weighing of reasons -- Limited Balancing. The Principle of Human Dignity and its Inviolability -- Balancing Rights and Interests. On Schauer's Asymmetry Thesis -- To Balance or not to Balance: The Quest for the Essence of Rights -- An argument for the proportionality test in concrete: challenging the margin of appreciation doctrine from a gender perspective in intersection with poverty -- Proportionality Test and Constitutional Social Rights Adjudication -- "Thou shalt balance" : Making sense of the delegation of the proportionality testing to the end users of law.